(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the removal of calcium hydroxide paste from simulated curved canals using Easy Clean®. Fifty acrylic blocks with simulated curved lateral channels were used in the cervical, middle and apical thirds. The blocks were prepared using the ProDesign Logic® system. Initially, they were explored with a 10mm k-file file until the foramen exit. Then the Glide Path and the patency were defined – Glide File 25.01 and the final modeling was carried out with the file 25.05 up to the working length. The irrigation procedure was performed with saline throughout the preparation of the artificial canal with a disposable syringe and NaviTip® needle (NaviTip®, Ultradent®, Brazil). After completing the canal preparation, the specimens were dried with absorbent paper cones. Calcium hydroxide paste was inserted into the channels along their entire length. To remove the calcium hydroxide paste, the irrigating solution was stirred for 20 seconds with the aid of the Easy Clean® instrument coupled to a contra-angle set at low speed. This protocol was repeated 3 times, totaling 9 ml of irrigating solution and 1 minute of agitation. In 40 resin blocks (95% of the sample) there was total cleaning after irrigation and use of Easy Clean®. In 10 blocks (5% of the sample) UltraCal XS® remained, mainly in the apical third of the blocks, which still presented a considerable amount of residues.